HUBUNGAN ANTARA KREATIVITAS DENGAN PRESTASI BELAJAR SISWA - Dindin Komarudin (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2011)
One of aspects that can encourage students in order to be able to get achievement in education is creativity, i.e., a mental process in which experiences in the past is recombined often with a form changed. This research is done to know the correlation between creativity and study achievement. Related to it, non-experimental with correlation method is used. Creativity is measured by using verbal and figural creativity test composed by Torrence (Munandar, 1977) with ordinal scale study achievement is measured by looking the cumulative value of student reports in the last of semester which is put into the ordinal scale. Because both the scales have interval scale, so the hypothesis test used is the formula of Pearson correlation. Based on the result of significance test, it is gotten that thitung is 1,07. With standard of significance α=0,05and (dkn-2) =44for the test of both sides, it is gotten ttabel =2.02. The criteria test used is repelling H0 if thitung is the same as or higher than ttabel. However thitung = 1,07is not higher than ttabel =2,02 on the standard of significance=0,05,therefore H0 is accepted. So, it can be said that there is no the significant positive correlation between creativity and study achievement.